Co-projecto em FPGA da MAC IEEE 802.11p para comunicações veiculares - Silva, Manuel José Alves Ventura da (2012)
The advancements and dissemination of telecommunication technologies has caused them to be employed more and more in our day-to-day life. Recently, these technologies have been applied to vehicles, as a way of not only improving driving safety but also the drivers' and passengers' comfort. If vehicular communications are to become a reality, communication standards must be created in order to allow the development of compatible communication platforms, while also serving as a basys for application development. The standards IEEE WAVE, alongside the IEEE 802.11p amendment, were proposed in order to meet these demands and address some of the speci c issues with vehicular networks, such as short connectivity times and the highly dynamic nature of the propagation environment. This thesis ts within the HEADWAY project, the goal of which is the creation of a device that will perform communication between vehicles. In order to incorporate every layer of the WAVE (Wireless Access in Vehicular Environments) protocol stack, a development platform was conceived that will enable the creation of a standardized communications system for vehicles. The development platform created features an antenna, RF modules, DAC and ADC circuits, an FPGA, a general purpose microprocessor and a GPS module. This work is focused in the development and implementation in FPGA of a MAC layer in accordance with the WAVE standards. The MAC layer's di erent functionalities were divided according to their complexity and execution time, causing our MAC's division in Upper MAC (UMAC) and Lower MAC (LMAC). The UMAC will be implemented in software (C) running in an FPGA embedded microprocessor and will contain the MAC's functions that are more complex, algorithmically speaking, but are not required to be excuted in a very short time interval, such as frame processing and decoding. The LMAC will be implemented by VHDL modeled hardware logic and will perform time critical functions, such as the timestamping of received frames, and complex calculations that bene t from the paralelism o ered by hardware logic, such as CRC computation and error checking. This MAC layer was implemented in an FPGA and its mechanisms were validated.